234k views
4 votes
Question 7 (1 point)

(01.02)
Given that f(x) = 5x - 10 and g(x) = x+3, solve for f(g(x)) when x= -1.(1 point)

-30

0

10

12

1 Answer

1 vote

Answer:

0

Explanation:

f(x) = 5x - 10

g(x) = x + 3

To find f(g(x)), plug g(x) into f(x).

f(g(x)) = 5(x + 3) - 10

f(g(x)) = 5x + 15 - 10

f(g(x)) = 5x + 5

Now that you have f(g(x)), you can find f(g(-1)).

f(g(-1)) = 5(-1) + 5

f(g(-1)) = -5 + 5

f(g(-1)) = 0

User SantiagoIT
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.